Strategic cost management and its role in reducing costs using business process reengineering A case study at City Steel Industrial Company - Osman Abdelkader Hama Amin; Rojan Abdullah Hama Amin (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
With increasing intensity of competition and the tremendous advances in technology make companies focus on cost and try to reduce it to achieve competitive advantages. Reducing costs is one of the most important concerns of strategic cost management, which seeks to achieve through a set of modern methods in the field of cost and managerial accounting. The integration of business process reengineering and contemporary approaches to each other, which has more positive impact on reducing cost than using these two approaches alone, the research aims to apply process reengineering technology through the use of strategic cost management techniques to improve the value of products and services to achieve cost reduction. The (City Steel) company for smelting and iron industry was selected as one of the companies that suffer from high costs because of competition products as a result of the opening of the Iraqi market to the rest of the markets at competitive prices, which led to incurring significant losses. One of the most important conclusions reached by the research is the possibility of applying the business process reengineering in the company that surveyed, its applying leads to a savings in the production costs of both producers in the case of business reorganization which is reflected on the profitability of the company and gain on its competitive advantage. One of the most important recommendations of the research is the company’s adoption of the process reengineering because of its positive effects being the best choice for our competitive environment in Iraq in the presence of competing companies in manufacturing, and it entails many advantages, especially reducing costs and the trend towards modernizing production lines by the company.